API-Led Connectivity Architecture : A Comprehensive Framework for Enterprise Integration - Gokul Babu Kuttuva Ganesan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
API-led connectivity architecture represents a transformative approach to enterprise integration, offering organizations a structured methodology for connecting systems, data, and applications through purpose-built APIs. This architecture implements a three-tiered framework comprising System APIs for core system access, Process APIs for business logic orchestration, and Experience APIs for end-user interaction. The methodology emphasizes security, scalability, and reusability while enabling organizations to achieve digital transformation objectives efficiently. This article examines the architectural principles, implementation strategies, and organizational benefits of API-led connectivity, providing insights into how enterprises can leverage this approach to create robust and adaptable integration solutions.
Keywords: Enterprise Integration; API Architecture; Digital Transformation; System Orchestration; Integration Framework